Nanorobotics: An Impressive Technological Trend - Priyanka D, Yelkote; Shafi, Sameer; Vaishnavi S, Ghodake; Mohini A, Gurav; Ayesha N, Siddiqui; Madhuri M, Phulari; Rohini U, Santé (Asian Journal of Pharmaceutical Research and Development, 2023)
Nanorobotics is a new and exciting field of nanotechnology that operates at the atomic, molecular, and cellular levels. These tiny robots are made up of carbon and have a toolkit containing useful components such as a medicine cavity for holding medicine, a micro camera, a payload, a capacitor, and a swimming tail. Nanorobots have special sensors that can detect target molecules in the human body, making them useful for diagnosing and treating various diseases such as cancer, diabetes, atherosclerosis, kidney stones, and more. While nanorobots are still being researched, some early molecular models of these medically programmable machines have been tested. This review covers various aspects of nanorobots, including their introduction, history, ideal characteristics, approaches in nanorobotics, basis for development, tool kit recognition, and retrieval from the body, as well as their applications in diagnosis and treatment.